Tecnologia cuidativo-educacional para adolescentes no puerpério - SILVA, Milka Borges da (2024)
Introduction: Several sources of knowledge influence adolescents in adopting self-care practices in the postpartum period. However, difficulties in health education guidelines can contribute to the adoption of harmful behaviors and barriers to maintaining self-care. In this sense, the use of care-educational technologies plays a fundamental role in promoting self-care. Objective: To develop cards with messages and images about self-care for adolescent postpartum women for use in a WhatsApp group, as a care-educational technology. Methods: This is a methodological study, conducted in three stages: stage 1: integrative literature review, stage 2: development of cards and messages about self-care for adolescent postpartum women for use in a WhatsApp group, stage 3: validation of content and appearance, carried out in two phases, with experts in content and communication and media. After the development of the first version, adjustments were made to the cards and messages based on the experts' comments and suggestions, resulting in the second version. The degree of agreement among experts was calculated using the Content Validity Index (CVI) and Appearance Validity Index (IVA). The study complied with the ethical aspects of research with human beings and was approved by the Research Ethics Committee of the Federal University of Maranhão. Results: In the first stage, it was identified that the guidelines on self-care for adolescent postpartum women are related to hygiene, use of homemade recipes, nutrition, vitamins, breast care, breastfeeding, sexual intercourse, reproductive planning, physical activity, weight loss, rest, support network and mental health. In the second stage, cards with messages and images based on the Self-Care Theory and the content identified in the previous stage were created for use in a WhatsApp group, totaling 25 cards in the first version. In stage 3, the first version of the cards with messages and images was simultaneously sent to the experts in content and appearance. This process took place between February and March 2024. Regarding the content, although the CVI was 1.0, the content and appearance experts made pertinent comments and suggestions, making it necessary to review the messages and cards, and the second version was prepared, followed by the second phase of validation between April and June 2024. In the first phase of evaluation of the cards and messages, an CVI of 1.00 and a VAT of 0.80 were obtained, after adjustments, the second phase occurred, in which an overall CVI of 1.00 and an overall VAT of 0.93 were obtained. In this sense, 25 cards were prepared, organized into: Welcome message; Presentation of the researcher; Definition of Self-care, among other topics. Conclusion: The study allowed the identification of content related to the self-care of adolescent postpartum women and the preparation of cards with images and messages to be used in a WhatsApp group of the care- educational technology type, which were considered valid in terms of content and appearance by the experts.